Penerapan Tri Hita Karana sebagai Desa Multikultur dan Implikasinya Terhadap Pendidikan Agama Hindu di Desa Adat Piling, Kecamatan Penebel, Kabupaten Tabanan - Ida Bagus Kade Mahandika; Gede Rai Parsua; I Putu Suweka Oka Sugiharta (Samsara Institute Publisher, 2026)
This study aims to analyze the implementation of Tri Hita Karana as a philosophical foundation for developing a multicultural community and to examine its implications for Hindu Religious Education in Piling Traditional Village, Penebel District, Tabanan Regency. The social life of Piling Traditional Village is characterized by religious and sociocultural diversity, requiring the cultivation of harmony, tolerance, mutual cooperation, and respect for differences. In this context, Tri Hita Karana, which emphasizes harmonious relationships between humans and God (parhyangan), humans and fellow human beings (pawongan), and humans and the natural environment (palemahan), provides a relevant philosophical framework for fostering an inclusive and harmonious multicultural society. This study employs a qualitative approach with a descriptive-interpretive research design. Data were collected through observation, in-depth interviews, and documentation involving traditional leaders, religious leaders, community members, and stakeholders involved in Hindu Religious Education. Data analysis was conducted through data reduction, data presentation, conclusion drawing, and philosophical interpretation of the community's social and religious practices. The findings indicate that the implementation of Tri Hita Karana in Piling Traditional Village is not limited to Hindu religious activities but is also manifested in patterns of social interaction, mutual cooperation, respect for religious differences, environmental awareness, and community participation in various social activities. The pawongan dimension plays a particularly significant role in fostering harmonious relationships among people of different religious backgrounds, while parhyangan and palemahan provide spiritual and ecological foundations for communal life. These practices have significant implications for Hindu Religious Education, particularly in developing learning processes that go beyond the transmission of religious knowledge toward the formation of tolerant, inclusive, humanistic, ecological, and pluralism-oriented character. Therefore, Tri Hita Karana can be reconstructed as a contextual and multicultural paradigm for Hindu Religious Education, in which religious values are not confined to the doctrinal domain but are transformed into lived.